Smoking-related outcomes and associations with tobacco-free policy in addiction treatment, 2015–2016. (1st October 2017) - Guydish, Joseph; Yip, Deborah; Le, Thao; Gubner, Noah R.; Delucchi, Kevin; Roman, Paul
Highlights: Clients in 25 treatment programs were assessed for smoking-related outcomes. Few differences in outcomes were found between 2015 and 2016. Clients in programs with tobacco-free grounds smoked fewer cigarettes per day. Staff and clients smoked together less often in programs with tobacco-free grounds. Comparison of pre- and post-policy implementation showed improvement in outcomes. Abstract: Objective: This study assessed changes in smoking-related outcomes in two cross-sectional samples of clients enrolled in addiction treatment and whether tobacco-free grounds policies were associated with smoking-related outcomes. Method: Clients in 25 programs were surveyed in 2015 (N = 1176) and 2016 (N = 1055). The samples were compared on smoking prevalence, cigarettes per day (CPD), thinking of quitting, past year quit attempts, staff and clients smoking together, attitudes towards quitting, and tobacco-related services. Second, programs with (n = 6) and without (n = 17) tobacco-free grounds at both time points were compared on smoking-related outcomes. Last, we examined changes in these measures for two programs that adopted tobacco-free grounds between 2015 and 2016. Results: There was one difference across years, such that the mean score for the tobacco Program Service scale increased from 2.37 to 2.48 (p = 0.043, effect size = 0.02). In programs with tobacco-free grounds policies, compared to those without, both CPD and the rate of staff and clients smoking together were significantly lower. In the two programs where tobacco-free grounds were implemented during study years, client smoking prevalence decreased (92.5% v. 67.6%, p = 0.005), the rate of staff and clients smoking together decreased (35.6% v. 4.2%, p = 0.031), mean CPD decreased (10.62 v. 8.24, p < 0.001) and mean tobacco services received by clients increased (2.08 v. 3.05, p < 0.001). Conclusion: Addiction treatment programs, and agencies responsible for licensing, regulating and funding these programs, should implement tobacco-free grounds policies.